P‐11.13: The Development of 27inch TFT LCD Large Size Outdoor Application. (4th October 2019) - Qiang, He; Yewen, Wang; Chun, Ye; Aishi, Chen; Shengping, Shi; Yanting, Duan; Wei, Ding; Jiacheng, Xu; Zhijun, Wang
Abstract : This paper introduces the development and performance of 27 inch TFT LCD FHD GDM vertical screen for outdoor which was successfully fabricated with IGZO process. A systematic research of properties, problems and the corresponding solutions of developing large size professional display applied outdoor is demonstrated. Moreover, the application of IGZO‐TFT device in professional display will become prosperous.